FAKTOR YANG BERHUBUNGAN DENGAN PEDAGANG MINUMAN DALAM MEMILIH JENIS ES BATU DI PASAR TRADISIONAL SENTRAL KOTA MEDAN TAHUN 2012 - Megawati *; Surya Dharma; Wirsal hasan (Lingkungan dan Kesehatan Kerja, 2014)
Water highly an important role in influencing human health, because it can be a medium of transmission of various diseases. therefore water is used to meet the needs of daily that must be protected from pollution especially it for drinking. Ice is kind of snacks were popular community drink Ice cubes were frozen water, which is cooled below 0 ° C. Ice cubes were used as a complement or an additive beverage drinks. There were several types of ice cubes one ice block and ice crystals. The purpose of this study was to determine the factors relate with beverage vendors in selecting the type of ice cubes in the central market of Medan. This research is Analytical . Population in this study were 94 people with 48 samples. Sample were taken by using systematic random sampling. Of this research note that the percentage of respondents elementary education level by 4.2%, 12.5% junior high, high school 75.0%, 8.3% PT. Respondents using the ice crystals were 60.4% and 39.6% ice beam. Respondents who had a good knowledge of 81.3%, of respondents who had a good attitude to the category of 52.1%, of respondents who had a good measure of 75.0%. There is a relation between education and type of ice that used α (0.076 <0.1) means that Ho is rejected, there is a relationship of knowledge with ice cubes used α (0.001 <0.1) means that Ho is rejected, there is a relationship with the kind of attitude that used ice cubes α (0.004 <0.1) means that Ho is rejected, no relation to the type of action used ice cubes α (0.001 <0.1) means that Ho is rejected. Traders expected the drinks were still using ice blocks that do not use ice beamagain.Key words: Type Ice Cubes